Quo vadis European biofuel policy: The case of rapeseed biodiesel - Gernot Pehnelt; Christoph Vietze (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
The European Unions (EU) Renewable Energy Directive (RED) continues to be the focus of much debate over the validity of biofuel sustainability. The debate is driven in part by ongoing concerns of transparency and regional variations of emissions from feedstock cultivation and processing. In a working paper, Pehnelt and Vietze (2012) undertook a general analysis of rapeseed biodiesel greenhouse gas (GHG) savings. In light of the recent effort to decentralize assessments to regional (i.e. Member State) authorities to assess the sustainability of biofuel feedstocks, we have done the same for three Member States, incorporating the comments and critique we received on our latest working paper (Pehnelt and Vietze 2012). Using publicly available cultivation and production figures from Germany (the largest producer and consumer of rapeseed biodiesel), Poland and Romania, we analyse the greenhouse gas (GHG) emissions savings of rapeseed biodiesel which we then compare to the values of GHG savings identified in the RED. Under average conditions and conservative assumptions on N2O emissions, German rapeseed biodiesel meets the GHG savings requirements of 35 percent in the RED. However, in years with unfavourable weather conditions and lower yields, German rapeseed biodiesel may fail to reach the 35 percent threshold even with efficient production technologies in the subsequent steps of the supply chain. Taking into account higher N2O emissions due to fertilizer input as suggested by some researchers, German rapeseed biodiesel clearly fails to fulfil the 35 percent criterion required by the RED. Meanwhile, in no instance Polish or Romanian rapeseed biodiesel meet the RED's 35% GHG savings threshold. The assessment of the sustainability of rapeseed biodiesel heavily depends on the very production conditions and assumptions regarding the N2O field emissions. As a matter of fact, not every liter of rapeseed biodiesel produced in the EU is sustainable in the sense of RED. Therefore, the use of standard values (e.g. default values) in order to categorize rapeseed biodiesel - or any other biofuel - as sustainable or not is not justifiable. With renewable energy strategies proliferating throughout the world, the validity of technical criteria has become increasingly critical to the success of these strategies - particularly the fiercely debated RED. The application of technical criteria remains inconsistent, and in the case of the RED, resulting in unreliable assessments of biofuel feedstocks and heated debates over the authority of these assessments.
Keywords: F14; F18; O13; Q01; Q15; Q27; Q56; Q57; 330; biodiesel; biofuel; default values; GHG-emissions; rapeseed; renewable energy directive; typical values